General and Highly Efficient Iron-Catalyzed Hydrogenation of Aldehydes, Ketones, and α,β-Unsaturated Aldehydes - Fleischer, Steffen; Zhou, Shaolin; Junge, Kathrin; Beller, Matthias (Angewandte Chemie International Edition, 2013)
EnvIRONmentally friendly: The title hydrogenation of aldehydes, ketones, and α,β‐unsaturated aldehydes is reported. In the presence of the catalyst 1, primary, secondary, and allylic alcohols were obtained in good to excellent yields under mild reaction conditions. The catalyst is easily and inexpensively prepared, and is also stable to air, water, and column chromatography.